Factors Associated with Mortality from Renal Failure in Brazil: A Descriptive Epidemiological Study - Maria Anacleto; Jessica Silva; Millena Gonçalves; Mateus Antunes; Diêgo Andrade (Shahrekord University of Medical Sciences, 2022)
Background and aims: The incidence of renal failure (RF) is growing in Brazil, resulting in increased public spending and negatively affecting the public health, which can lead to patient death. Identifying factors associated with mortality from this condition can help to characterize susceptible populations; therefore, institutional and governmental measures can be adopted for prevention and treatment. Materials and Methods: Descriptive epidemiological study using secondary data from Brazilian database (DATASUS). Deaths from RF between 2009 and 2019 and characteristics such as color/race, gender, education, region, and age group of the individuals were analyzed. Results: Since 2016, there has been a reduction of approximately 2% per year in the RF case fatality rate. North, Northeast, and Southeast regions had the highest case fatality rate, 13.6%, 13.17%, and 12.84%, respectively, which may be associated with high prevalence of chronic-degenerative diseases. The elderly had the highest case fatality rates, ranging from 9.67% in individuals aged 50-59 years to 27.52% in the elderly over 80 years. Children under 1 year of age had a high case fatality rate of 15.03%. Moreover, the case fatality rate for individuals with education levels above 12 years of schooling was 0.50%, while the case fatality rate for individuals with 1 to 3 years of schooling was 3.52%, which is seven times higher. Case fatality rates of indigenous populations in the South and Southeast regions were 12.0% and 16.5%, approximately 20% higher than other populations. Conclusion: The presence of chronic-degenerative diseases, age above 50 and below 1 (elderly and preterm newborns), low level of education and being indigenous are factors associated with mortality from RF in Brazil.